Learning to Die: Analysis of The Cultural Role of Voluntary Death - Martini, Niccolò (Journal of Advanced Research in Social Sciences, 2020)
Voluntary death is a morally and legally grey area in many countries around the world. In my research I studied the topic of euthanasia and assisted suicide in Italy. Specifically, I analyzed the relationship between collective law and individual morality using as case study the phenomenon of voluntary death, which has been making people talk about itself in recent years precisely because of its as yet undefined nature. Using a qualitative approach i.e., semi-structured interview, I listened the voices of a representative sample of Italian doctors in order to collect the opinion of the medical class i.e., the social group that would be most affected by the possible legalization of euthanasia. It has emerged, among other things, that Italy lacks a real education to death. The research has opened a reflection on the range of voluntary death within a Nation where it is illegal. Numerous studies have determined the enormous symbolic baggage present within the concept of death, but in the study of the legalization of voluntary death a new factor has emerged: a legalization is not desired until the population receives a real education on the idea of having to die. Like sex, death is still a taboo in many societies around the world. Is it therefore necessary to fulfill a death education before even start to talk about creating a general law. This research has exalted not only a cultural deficiency but also the desire to remedy it through education, in order to exorcise the fear of an event that sooner or later everyone has to face.